2001
DOI: 10.5547/issn0195-6574-ej-vol22-no3-3
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Market Power Mitigation Strategies in Colorado's Electricity Industry

Abstract: We apply an algorithm that optimizes the generation dispatch for a dominant firm to Colorado's electricity market and show that the dominam electn'city generation firm can strategically congest transmission into the region to receive a maximum price over 50% of the time. When it does not get the maximum price, the dominant firm still receives an average markup more than 10% over the competitive price. We use this model to show how mitigation strategies such as enhancing the transmission grid, divesting the dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Such limit-pricing is credited with keeping a lid on prices in the U.K. [69]. Meanwhile, Stackelberg models have represented interactions between large power producers ("leaders") and one or more "followers" (smaller generators and/or the ISO) [33], [34], [50], [67].…”
Section: Applications Of Alternative Interactions To Power Marketsmentioning
confidence: 99%
“…Such limit-pricing is credited with keeping a lid on prices in the U.K. [69]. Meanwhile, Stackelberg models have represented interactions between large power producers ("leaders") and one or more "followers" (smaller generators and/or the ISO) [33], [34], [50], [67].…”
Section: Applications Of Alternative Interactions To Power Marketsmentioning
confidence: 99%
“…Meanwhile, a Stackelberg game represents interactions between large and small companies over quantities of products [14]. It is usually used with oligopolies with one or two large dominant companies [15]. Moreover, the Supply Function Equilibrium (SFE) represents companies that compete in supply functions with different prices for different quantities.…”
Section: Introductionmentioning
confidence: 99%
“…Willems (2002) studied a very similar market model to that of Borenstein et al and investigated the role of the network operator for promoting competition among the generators. Quick and Carey (2001) applied the "dominant firm priceleadership model" to assess market power in Colorado's electricity industry and showed that strategies exist to reduce market power. Leautier (2000) studied regulatory contracts for the operators of transmission networks and proposed a regulatory contract that induces network operators to "optimally" expand the grid.…”
Section: Introductionmentioning
confidence: 99%